Analisis postur kerja pada aktivitas manintiang menggunakan metode REBA, RULA dan OWAS pada pengolahan emas tradisional tanpa merkuri endapan alluvial Logas, Riau - Sugiono, Nana; Surya, Roberta Zulfhi; Sartika, Laura Dwi Ayu; Atryes, Viola (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Manintiang is a manual activity of separating gold from impurity particles (iron ore, silica, and ilmenite) through gravity, fluid pushing force, and friction force on the surface of the gold panning. Manual activities with an average weight of gold panning, water, and gold concentrate weighing 5–8 kg have the potential to cause musculoskeletal disorders (MSDs) in the short term and cumulative trauma disorders (CTDs) in the long term. This research aims to analyze the work posture of the "Manintiang" activity so that it can determine the potential for work injuries, identify unnatural work postures that cause discomfort at work, and identify work postures that have the potential to cause work accidents. The analysis methods used are REBA (Rapid Entire Body Assessment), RULA (Rapid Upper Limb Assessment), and OWAS (Ovako Working Analysis System) and use the Angle Meter 360 application version 1.9.3 for IOS. The results of this research is RULA = 7, REBA = 8, and OWAS = 2. Manintiang with a working position looking down and moving the gold panning back and forth is an unnatural working position, repetitive movements, and excessive muscle tension, which causes MSDs and CTDs.